Efektivitas Program Tadabbur Al-Qur’an dalam Peningkatan Akhlak Siswa di MI Al Fithrah Surabaya - Moh. Taufiq (Journal on Education, 2020)
Tadabbur Al-Qur'an is one of the teaching programs in the junior high school environment which aims to foster and develop polite and harmonious relationships between students and Allah, between students and each other, and between students and their environment. Many factors influence the success of a person's life, one of which is having good morals such as wisdom, generosity, renewal, steadfastness, chivalry, justice and others. The Al-Qur'an Tadabbur Program at MI Al Fithrah Surabaya is a form of madrasah program in an effort to shape student morality, the authors submit this evidence after the authors conducted research at the madrasah. The type of research used in this research is quantitative "pre-experimental design" technique, namely research using "one group design pre-test post-test" design which is then followed by statistical analysis of the "t" test (Fisher's Formula) to analyze the data. The results showed that there were significant differences between the morals of the students in the experimental group and the control group. Based on the analysis of the data obtained: the Al-Qur'an Tadabbur Program category is quite good so it is said to be effective. This difference can be seen from the increase in the average score of the Experiment group from 82.50 (Pre-Test) to 87.5 (Post-Test ) and the control group from 6.67 (Pre-Test) to 12.5 (Post-Test). This shows a significance level of 5. In the calculation results of the t test, it is obtained to be 45.83. This figure is far greater than tt at a significance level of 5%, namely 2.71 and a significance level of 1%, namely 2.02 (2.71 <45.83> 2.02). Thus it can be concluded that the application of the Al-Qur'an tadabbur program is quite effective in improving the morals of class 1 MI Al Fithrah Surabaya students.